A kind of lac-potassium pyrosulfite drug-carrying nanoparticles and its preparation method and application
The shellac-potassium metabolites prepared through microfluidic control technology solve the problem of unstable SO2 release in fruit wine, and achieves the slow release of potassium metabolic acid, ensuring the bactericidal and antioxidant effect of fruit wine and the stability of the wine body.
Patent Information
- Application Number
- CN202310252773.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-15
AI Technical Summary
When using SO2 in the brewing and storage of fruit wine, there are problems of fruit wine oxidation and poor stability of the wine body, and potassium metabisulfite needs to be added frequently to ensure the effective content of SO2.
Microfluidic control technology is used to prepare shellac-potassium metabisulfite drug-loaded nanoparticles. Through the anti-solvent co-precipitation principle, potassium metabisulfite crystallizes and is embedded in shellac, achieving its slow release in the wine body.
The continuous and slow release of potassium metasulfite is achieved, ensuring that the SO2 content in the fruit wine is always maintained at a concentration with bactericidal and antioxidant effect, avoiding the disadvantages of frequent additions, and improving the stability and quality of the wine body.
Smart Images

Figure CN116478784B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drug-carrying nanoparticles, and specifically relates to shellac-potassium pyrosulfite drug-carrying nanoparticles and a preparation method and application thereof. Background Art
[0002] For example, the food functional factors that play a leading role in functional foods such as curcumin and β-carotene include essential fatty acids or oils, vitamins, phytochemicals, active peptides, etc. While they have multiple excellent biological activities such as anti-oxidation, anti-obesity, anti-virus, anti-cancer, anti-inflammatory, and anti-aging, they are prone to deterioration due to their poor water solubility or fat solubility, chemical or thermal instability, and susceptibility to the pH value, oxygen or salt ions in food, which seriously limits their application in food. At present, food-grade polymer nanoparticles have been designed to effectively encapsulate, preserve and deliver a certain number of functional factors. For example, shellac resin has strong adhesion, good gloss, UV stability, good electrical insulation properties, both thermoplastic and thermosetting, soluble in alcohol and alkali, oil-resistant, acid-resistant, non-toxic and non-irritating to humans, and can be used as varnish, polish, adhesive, insulation material and molding material, etc., and is widely used in defense, electrical, coating, rubber, plastic, medicine, leather, papermaking, printing, food and other industrial sectors.
[0003] SO2 is an antioxidant commonly used in winemaking processes internationally. It has the functions of inhibiting the growth of microorganisms and bacteria, preventing oxidative browning and corruption. It has been reported that SO2 can preserve fruits and effectively extend their shelf life by inhibiting the activity of enzymes such as polyphenol oxidase. However, in the prior art, when SO2 is used for preservation, there are still phenomena such as oxidation of fruit wine and poor stability of the wine body. When SO2 is added to fruit wine brewing, it is only added in individual links, and the degree of antioxidant protection for the wine body is insufficient. Correct use of SO2 can make the brewing and storage of fruit wine go smoothly and improve the quality of wine. The effective content of SO2 needs to be strictly controlled during the brewing process. Too little addition affects its bactericidal and antioxidant effects and also causes harm to human health. According to the provisions of the "National Food Safety Standard for the Use of Food Additives" (GB2760-2014), the residual amount of SO2 is controlled within 250mg / L. Free SO2 plays a major antioxidant role, and its content is usually obvious when it is 20-40mg / L. It is known that the use of potassium metabisulfite can produce SO2 during the fermentation process to protect the wine body. However, in order to ensure that the SO2 in the wine body can always have an excellent antioxidant effect, it is necessary to consider how to achieve the continuous release of SO2 at an appropriate concentration. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to design and provide a shellac-potassium pyrosulfite drug-carrying nanoparticle and its preparation method and application. The shellac-potassium pyrosulfite drug-carrying nanoparticle of the present invention overcomes the disadvantage of repeatedly adding a large amount of potassium pyrosulfite during the process of winemaking, aging, storage, etc., and provides a method for allowing potassium pyrosulfite to continuously and slowly release SO2, thereby ensuring that the SO2 content in the fruit wine always maintains a concentration with a bactericidal and antioxidant effect.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] A method for preparing shellac-potassium pyrosulfite drug-loaded nanoparticles comprises the following steps:
[0007] (1) dissolving shellac in ethanol to obtain a shellac solution, and filtering the solution through a membrane for later use;
[0008] (2) dissolving potassium pyrosulfite in ultrapure water to obtain a potassium pyrosulfite solution, and passing it through a membrane for later use;
[0009] (3) The total flow rate and the flow rate ratio of the aqueous phase to the organic phase of the shellac solution and the potassium pyrosulfite solution were controlled by a microfluidic method, so that the potassium pyrosulfite crystals were precipitated and embedded in the shellac to prepare shellac-potassium pyrosulfite drug-loaded nanoparticles.
[0010] Preferably, in step (1), the concentration of the shellac solution is 10-30 g / L.
[0011] Preferably, the concentration of the shellac solution is 20 g / L.
[0012] Preferably, in step (2), the concentration of the potassium pyrosulfite solution is 0-25 g / L.
[0013] Preferably, the concentration of the potassium pyrosulfite solution is 25 g / L.
[0014] Preferably, in step (3), the total flow rate of the microfluidic method is 30-40 mL / min, and the flow rate ratio of the aqueous phase: the organic phase is 1:3-1:5.
[0015] Preferably, the total flow rate is 36 mL / min, and the aqueous phase:organic phase flow rate ratio is 1:5.
[0016] The invention also provides shellac-potassium pyrosulfite drug-carrying nanoparticles prepared by the preparation method.
[0017] The invention also provides application of the shellac-potassium pyrosulfite drug-carrying nanoparticles prepared by the preparation method in preserving wine.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention adopts microfluidic technology and utilizes the principle of anti-solvent co-precipitation. Potassium pyrosulfite crystallizes and precipitates after encountering shellac solution and is embedded in shellac. The purpose is to allow potassium pyrosulfite to be slowly released in the wine body to achieve the effect of continuous preservation and anti-oxidation.
[0020] 2. Compared with other methods for synthesizing nanoparticles, the preparation method of the present invention has the advantages of uniform synthesized particle size of about 100 nm, good polydispersity index, high repetition rate, and large-scale preparation.
[0021] 3. The raw materials of the present invention are cheap and readily available, non-toxic and harmless, easy to operate, and reduce the amount of potassium pyrosulfite added during preservation, and avoid the disadvantage of repeated addition of potassium pyrosulfite, thereby well maintaining the quality of the wine.
[0022] 4. The encapsulation efficiency of the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared by the present invention is about 73.9%, and the drug loading amount is about 21.818%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments consistent with the present invention and, together with the description, serve to explain the principles of the present invention, in which:
[0024] Figure 1 The flowchart of the preparation method of shellac-potassium pyrosulfite drug-loaded nanoparticles of the present invention;
[0025] Figure 2 This is a comparison diagram of the appearance of shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 6 at the same total flow rate, different flow rate ratios, and different shellac concentrations;
[0026] Figure 3 It is a comparison chart of the particle size and polydispersity index of shellac-potassium pyrosulfite drug-loaded nanoparticles prepared at the same total flow rate, different flow rate ratios, and different shellac concentrations in Examples 1 to 3 of the present invention and Comparative Examples 1 to 6;
[0027] Figure 4 This is a diagram of the device for detecting SO2 of the present invention;
[0028] Figure 5 This is a transmission electron microscope (TEM) image of the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Example 1 of the present invention;
[0029] Figure 6 This is a scanning electron microscope (SEM) image of the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Example 1 of the present invention;
[0030] Figure 7 This is a Fourier infrared spectrum of the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Example 1 of the present invention;
[0031] Figure 8 This is an atomic force microscope (AFM) image of the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Example 1 of the present invention, wherein: Figure 8 a is the plan view of drug-loaded nanoparticles. Figure 8 b is the topographic map of drug-loaded nanoparticles;
[0032] Fig. 9 This is a dispersion diagram of shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Example 1 of the present invention in aqueous solution under different pH conditions;
[0033] Fig.10 The release of potassium pyrosulfite from the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Example 1 of the present invention is compared with that from Comparative Example 7.
[0034] Reference numerals:
[0035] A. Short-necked ball bottle; B. Three-way connecting pipe; C. Ventilation pipe; D. Straight tube condenser; E. Elbow pipe; F. Vacuum distillation receiving tube; G. Pear-shaped bottle; H. Gas scrubber; I. Right-angle elbow. DETAILED DESCRIPTION
[0036] The disclosure below provides many different embodiments or examples to implement different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed.
[0037] 1. Selection of potassium metabisulfite concentration
[0038] In order to make the drug loading and encapsulation rate of the prepared nanoparticles higher, it is more likely to synthesize drug-loaded nanoparticles through microfluidics, and consider increasing the concentration of potassium pyrosulfite. Potassium pyrosulfite is dissolved in ultrapure water as the aqueous phase of microfluidics, and shellac is dissolved in ethanol as the organic phase. When the aqueous phase and the organic phase meet in the microfluidic device, for the aqueous phase, the water content decreases, and the solubility of potassium pyrosulfite will decrease and precipitate. For the organic phase, the water content increases, which will cause shellac to precipitate. In order to make potassium pyrosulfite precipitate before shellac, shellac is then covered on potassium pyrosulfite for encapsulation. Using a saturated solution of potassium pyrosulfite is a better choice. According to experiments, the solubility of potassium pyrosulfite in water is approximately 25g / L, which is the most suitable concentration of potassium pyrosulfite.
[0039] 2. Preparation of lac-potassium pyrosulfite drug-loaded nanoparticles and screening of the optimal lac concentration and flow rate ratio during drug loading
[0040] Embodiment 1:
[0041] The flow chart of the preparation of nanoparticles of potassium pyrosulfite embedded in shellac involved in the present invention is as follows: Figure 1 As shown, the specific method is:
[0042] (1) Preparation of shellac solution: Weigh a certain amount of shellac, dissolve it in 95% ethanol, and ultrasonicate for 2-3 hours until the shellac solid is completely dissolved to obtain a shellac solution with a concentration of 20 g / L, which is a yellow transparent liquid.
[0043] (2) Preparation of potassium metabisulfite solution: Weigh a certain amount of solid white granules of potassium metabisulfite and dissolve them in ultrapure water to obtain a 25 g / L saturated potassium metabisulfite solution in the form of a colorless transparent liquid.
[0044] (3) Solution filtering: The 20 g / L shellac solution obtained in step (1) is filtered through a 0.22 μm organic membrane, and the shellac solution after filtering is placed in a 20 mL disposable syringe for later use; The 25 g / L saturated potassium pyrosulfite solution obtained in step (2) is filtered through a 0.22 μm water membrane, and the potassium pyrosulfite solution after filtering is also placed in a 20 mL disposable syringe for later use.
[0045] (4) Preparation of Shellac-Potassium Pyrosulfite Drug-Loaded Nanoparticles by Micro-Controlled Flow Method:
[0046] a) Fixing the solution: fix the syringe containing 20 g / L shellac solution on pump 1 of the microfluidic pump, and fix the syringe containing 25 g / L saturated potassium pyrosulfite solution on pump 2 of the microfluidic pump;
[0047] b) Install the chip lab: Place the microfluidic chip made of polymer materials in the middle of a specific polymer material clamp and fix it with screws at the four corners;
[0048] c) Connecting the solution and the chip lab: The two fixed solutions are connected to the chip lab using a specific polymer pipe and connector according to the principle of high flow rate and straight flow.
[0049] d) Exhaust air: Select pump 1, adjust the flow rate to 0.5 g / L, click Start, until the shellac solution flows out through the chip laboratory, click Stop; Select pump 2, adjust the flow rate to 0.5 g / L, click Start, until the saturated potassium pyrosulfite solution flows out through the chip laboratory, click Stop, and the air exhaust is completed;
[0050] e) Preparation of drug-loaded nanoparticles: The total flow rate was adjusted to TFR = 36 mL / min, the flow rate ratio was adjusted to FRR = 1:5 (aqueous phase: organic phase), and pump 1 and pump 2 of the microfluidic pump were turned on at the same time to prepare shellac-potassium pyrosulfite drug-loaded nanoparticles.
[0051] Example 2: The remaining steps are consistent with Example 1, except that the flow rate ratio is adjusted to FRR=1:4 (aqueous phase: organic phase).
[0052] Example 3: The remaining steps are consistent with Example 1, except that the flow rate ratio is adjusted to FRR=1:3 (aqueous phase: organic phase).
[0053] Comparative Example 1: The remaining steps were consistent with Example 1, except that the flow rate ratio was adjusted to FRR=1:2 (aqueous phase: organic phase).
[0054] Comparative Example 2: The remaining steps were consistent with Example 1, except that the flow rate ratio was adjusted to FRR=1:1 (aqueous phase: organic phase).
[0055] Comparative Example 3: The remaining steps were consistent with Example 1, except that the flow rate ratio was adjusted to FRR=2:1 (aqueous phase: organic phase).
[0056] Comparative Example 4: The remaining steps were consistent with Example 1, except that the flow rate ratio was adjusted to FRR=3:1 (aqueous phase: organic phase).
[0057] Comparative Example 5: The remaining steps were consistent with Example 1, except that the flow rate ratio was adjusted to FRR=4:1 (aqueous phase: organic phase).
[0058] Comparative Example 6: The remaining steps were consistent with Example 1, except that the flow rate ratio was adjusted to FRR=5:1 (aqueous phase: organic phase).
[0059] Depend on Figure 2 It can be seen that when the water phase has a high flow rate, white flocs or obvious large particles appear, that is, shellac is precipitated, indicating that drug-loaded nanoparticles are not synthesized, or aggregation and precipitation are caused due to charge reasons. Only when the flow rate ratio is 1:3-1:5 (aqueous phase: organic phase) no obvious white particles are precipitated.
[0060] The particle size and dispersibility index of the shellac-potassium pyrosulfite drug-loaded nanoparticles successfully prepared at different flow rate ratios were tested. Figure 3As shown, it can be seen that the drug-loaded nanoparticles prepared under the conditions of lac concentration of 20 g / L and flow rate ratio of 1:4 and 1:5 (aqueous phase: organic phase) have a higher dispersion index than that of lac concentration of 30 g / L, but a small particle size, and when the lac concentration is 30 g / L, it is easy to block the microfluidic chip. In contrast, the drug-loaded nanoparticles prepared under the condition of lac concentration of 10 g / L have a larger particle size but a similar dispersion index. According to experience, the higher the concentration of lac, the higher the encapsulation rate. Therefore, when the particle size and polydispersity index are within an acceptable range, a higher lac concentration is selected. Therefore, a flow rate ratio of 1:5 (aqueous phase: organic phase) and a lac concentration of 20 g / L are selected for the final preparation of drug-loaded nanoparticles.
[0061] The following tests were performed using the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared in Example 1:
[0062] 3. Encapsulation rate and drug loading detection
[0063] (1) Encapsulation efficiency detection
[0064] The encapsulation efficiency was defined as the portion of the initial antioxidant encapsulated by the shellac nanoparticles. The supernatant was separated and its concentration was calculated by measuring the SO2 concentration of the supernatant. After preparing 4 batches of drug-loaded nanoparticles, 30 mL of the supernatant was centrifuged at 12000 rpm for 30 min to allow the nanoparticles to settle. 10 mL of 25% phosphoric acid solution was added to the supernatant, which produced a white precipitate. The supernatant was centrifuged at 12000 rpm for 30 min again to allow the nanoparticles to settle completely. 30 mL of the supernatant was taken and the SO2 determination device was installed, as shown in FIG. Figure 4 :
[0065] a) Connect the right-angle elbow I to the vacuum pump (or the exhaust pipe), and let the cooling water flow into the straight condenser D. Connect the straight condenser D to the vacuum distillation receiving pipe F through the elbow E, and connect the elbow E to the pear-shaped bottle G through the vacuum distillation receiving pipe F; remove the pear-shaped bottle G and the gas scrubber H, add 20mL of hydrogen peroxide solution to the pear-shaped bottle G and 5mL of hydrogen peroxide solution to the gas scrubber H, and add 3 drops of mixed indicator solution to each. The solution immediately turns purple, and the sodium hydroxide standard solution is dropped until its color just turns to olive green, then reinstall it properly, and immerse the short-necked ball bottle A in an ice bath.
[0066] b) Connect the short-necked spherical bottle A, the vent tube C and the straight tube condenser D through the three-way connecting tube B, draw 20.00 mL of sample (liquid temperature 20°C), and add it into the short-necked spherical bottle A from the upper opening of the vent tube C. Then draw 10 mL of phosphoric acid solution and also add it into the short-necked spherical bottle A from the upper opening of the vent tube C.
[0067] c) Turn on the vacuum pump (or exhaust pipe) to make the air flow rate 1000mL / min~1500mL / min, and exhaust for 10 minutes. Remove the pear-shaped bottle G, and titrate with sodium hydroxide standard titration solution until the olive green color reappears. This is the end point, and record the number of milliliters of sodium hydroxide standard titration solution consumed. Use water instead of the sample to perform a blank test, and the operation is the same as above. Under normal circumstances, the solution in the gas scrubber H should not change color. If the solution turns purple, it is also necessary to titrate with sodium hydroxide standard titration solution to olive green, and add the volume of sodium hydroxide standard titration solution consumed to the volume of sodium hydroxide standard titration solution consumed in the pear-shaped bottle G. Calculation of results The content of free SO2 in the sample is calculated according to the following formula.
[0068]
[0069] Where:
[0070] X—the content of free SO2 in the sample, in milligrams per liter (mg / L);
[0071] c—the concentration of the sodium hydroxide standard titration solution, in moles per liter (mol / L);
[0072] V—The volume of sodium hydroxide standard titration solution consumed when measuring the sample, in milliliters (mL);
[0073] V0—the volume of sodium hydroxide standard titration solution consumed in the blank test, in milliliters (mL);
[0074] 32—the numerical value of the molar mass of SO2 in grams per mole (g / mol);
[0075] 20—The volume of the sample aspirated, in milliliters (mL).
[0076] The results are expressed as integers.
[0077] The encapsulation efficiency was calculated according to the following formula:
[0078]
[0079] C f : The amount of free drug;
[0080] C t : Total amount of drug in nanosuspension;
[0081] The encapsulation efficiency of shellac-potassium pyrosulfite drug-loaded nanoparticles was calculated to be 73.9%.
[0082] (2) Detection of drug loading
[0083] Weigh 0.7 mg of freeze-dried shellac-potassium pyrosulfite drug-loaded nanoparticles with an electronic balance, add hexanol and put into a numerically controlled ultrasonic cleaner, dissolve under ultrasonic power of 100w for 30min, and calculate its concentration by measuring the SO2 content of the solution. The calculation formula is as follows:
[0084]
[0085] W e : The amount of drug encapsulated by the drug-carrying nanoparticles;
[0086] W m :Total weight of drug-loaded nanoparticles.
[0087] The drug loading of shellac-potassium pyrosulfite drug-loaded nanoparticles was calculated to be 21.818%.
[0088] 4. Transmission electron microscopy (TEM) detection of shellac-potassium pyrosulfite drug-loaded nanoparticles
[0089] Before TEM detection, the sample needs to be dialyzed in ultrapure water for 24 hours through a dialysis bag (molecular weight cutoff 3.5kDa) until there is no organic solvent such as ethanol in the dialysis bag, and then freeze-dried. The dialyzed drug-loaded nanoparticles are taken and the micromorphology of the sample is evaluated by microscopy at an accelerating voltage of 100kV. The sample solution is diluted 10 times and deposited on a carbon-coated copper grid for transmission electron microscopy analysis. The software used to estimate the particle size was studied, such as Figure 5 As shown in the figure, it can be seen that the particle size is round and has an obvious shell-core structure, which proves that the encapsulation of potassium metabisulfite is successful and the dispersion is uniform.
[0090] 5. Scanning electron microscopy (SEM) detection of shellac-potassium pyrosulfite drug-loaded nanoparticles
[0091] The dialyzed and freeze-dried nanoparticles were observed using an ultra-high field emission scanning electron microscope and the particle size was measured using a program. Figure 6 As shown, it can be seen that the particle size of the shellac-potassium metabisulfite drug-loaded nanoparticles prepared under the optimal conditions is approximately 100 nm, and they are evenly dispersed and have uniform particle size.
[0092] 6. Fourier infrared spectroscopy detection of shellac-potassium pyrosulfite drug-loaded nanoparticles
[0093] The freeze-dried nanoparticles were pressed into tablets at wavelengths of 650 cm -1 and 4000cm -1 The spectral resolution is 4 cm -1 The test results are as follows: Figure 7 As shown, at 2750-3000cm -1There are double peaks in both blank shellac and drug-loaded nanoparticles, which are characteristic peaks of -CH3, generated by the stretching vibration of CH bond, at 2250-2500cm -1 There are double peaks in potassium pyrosulfite and drug-loaded nanoparticles in this range, which is caused by the cumulative double bond vibration of potassium pyrosulfite. In this range, shellac has no vibration peak, and there are no continuous double bonds in the shellac molecular structure, which proves the existence of potassium pyrosulfite in drug-loaded nanoparticles and the successful encapsulation of potassium pyrosulfite. -1 Peaks appeared in both blank shellac and drug-loaded nanoparticles in the range of 750-1000 cm -1 There are peaks in the range, which are the deformation vibrations of CH.
[0094] 7. Atomic force microscopy (AFM) detection of shellac-potassium pyrosulfite drug-loaded nanoparticles
[0095] Take 1-2 drops of the dialyzed drug-loaded nanoparticles with antioxidant properties prepared by the microfluidic device and drop them on a mica sheet attached to a glass slide. Add an appropriate amount of ultrapure water to dilute it without overflowing the mica sheet. Then suck out the excess and dilute it two or three times. Then blow dry the water with nitrogen, freeze and fix it, place the glass slide on the stage, adjust the probe and laser, etc., and detect the surface structure and properties of the drug-loaded nanoparticles through extremely weak atomic interaction forces, such as Figure 8 As shown in a, it can be seen that the nanoparticles are round and evenly dispersed. Due to the nitrogen blowing pressure, the nanoparticles are collapsed, and the measured particle size is slightly larger, but also around 100nm. Figure 8 b is the topographic map of drug-loaded nanoparticles, which can more intuitively show the properties such as particle size.
[0096] 8. Uniform dispersion of lac-potassium pyrosulfite drug-loaded nanoparticles in aqueous solutions at different pH conditions
[0097] like Fig. 9As shown, shellac nanoparticles are promising carriers. They are transparent and stable when dispersed in water. This characteristic of shellac nanoparticles is due to the carboxyl groups carried by shellac. In water with a low pH (e.g., pH = 2), most of the carboxyl groups on the surface of shellac nanoparticles are protonated and ionization is suppressed. The hydrophobicity of shellac causes the nanoparticles to aggregate and precipitate. In water with a neutral pH (e.g., pH = 7), the carboxyl groups on the surface of shellac nanoparticles are partially ionized to make the particles negatively charged. The electrostatic repulsion between them prevents the aggregation of nanoparticles. In water with a high pH (e.g., pH = 12), most of the carboxyl groups dissociate, making shellac soluble in water, so potassium pyrosulfite is directly exposed to alkaline solutions. Potassium pyrosulfite has no obvious color change under different pH conditions. Potassium pyrosulfite is stable at different pH levels and has a consistent color tone. Since the pH of fruit wine is not less than 2, it does not affect the application of shellac-potassium pyrosulfite drug-loaded nanoparticles in fruit wine. Therefore, the shellac-potassium pyrosulfite drug-loaded nanoparticles prepared by the present invention can be effectively used in an environment of pH=3-12.
[0098] 9. Release detection of shellac-potassium metabisulfite drug-loaded nanoparticles in fruit wine
[0099] Take 10 mL of the dialyzed shellac-potassium metabisulfite drug-loaded nanoparticle solution, add it into 100 mL of 13% ethanol, and detect the SO2 content at 3 h, 6 h, 9 h, 12 h, and 24 h.
[0100] Comparative Example 7: Take 7.39 mL of 25 g / L potassium metabisulfite solution, add it into 100 mL of 13% ethanol, and test the SO2 content at 3 h and 6 h respectively.
[0101] From the release test experiment of the particles of Example 1 and Comparative Example 7 in fruit wine, it can be seen that the potassium pyrosulfite without encapsulation will release more than 90% within 3 hours and basically release completely in about 6 hours, while the encapsulated potassium pyrosulfite can be continuously and slowly released within 24 hours. Fig.10 Using a pH of 7 will make the shellac easy to decompose, while the pH of fruit wine is generally between 3-4, which will slow down the decomposition rate of shellac and make the sustained release time longer.
[0102] Those skilled in the art will readily appreciate other embodiments of the invention after considering the specification and practicing the invention herein. The invention is intended to cover any variations, uses or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art of the invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the claims.
[0103] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A method for preparing shellac-potassium pyrosulfite drug-loaded nanoparticles, characterized in that: The following steps are involved: (1) dissolving shellac in ethanol to obtain a shellac solution, and filtering the solution through a membrane for later use; (2) dissolving potassium pyrosulfite in ultrapure water to obtain a potassium pyrosulfite solution, and passing it through a membrane for later use; (3) controlling the total flow rate and the flow rate ratio of the aqueous phase to the organic phase of the shellac solution and the potassium pyrosulfite solution by a microfluidic method, so that the potassium pyrosulfite crystals are precipitated and embedded in the shellac, thereby preparing shellac-potassium pyrosulfite drug-loaded nanoparticles; In step (1), the concentration of the shellac solution is 10-30 g / L; In step (2), the concentration of the potassium pyrosulfite solution is 25 g / L; In step (3), the total flow rate of the microfluidic method is 30-40 mL / min, and the flow rate ratio of the aqueous phase: the organic phase is 1:3-1:
5.
2. The method for preparing shellac-potassium pyrosulfite drug-loaded nanoparticles according to claim 1, characterized in that: The concentration of the shellac solution is 20 g / L.
3. The method for preparing shellac-potassium pyrosulfite drug-loaded nanoparticles according to claim 1, characterized in that: The total flow rate was 36 mL / min, and the flow rate ratio of the aqueous phase to the organic phase was 1:
5.
4. Shellac-potassium pyrosulfite drug-loaded nanoparticles prepared by the preparation method according to any one of claims 1 to 3.
5. Use of shellac-potassium pyrosulfite drug-loaded nanoparticles prepared by the preparation method according to any one of claims 1 to 3 in the preservation of alcoholic beverages.
Citation Information
Patent Citations
Self-assembled protein nanoparticles as well as preparation method and application thereof
CN113332165A
Compact starch-based nanoparticles as well as preparation method and application thereof
CN114957808A